Biomass and Productivity of 4.5 Year-Old Acacia mangium in Sarawak - Tsai, Lim Meng (1986)
Acacia mangium, one of the main spices used for forest plantations as well as reforestation in Malaysia, has been selected on account of its rapid growth and ability to overcome competition from weeds. A 4.5 year-old plantation stand in Sarawak had a density of 1084 trees/ha and a top height of over 20 m. The dbh of the trees ranged from 4.3 cm to 24.2 cm and averaged 14.3 cm. Regression of branch, stem and total above-ground biomass on dbh produced equations with correlation coefficients, r, of over 0.95. The biomass of the stand was estimated at 82.1 tonnes/ha. The mean annual increment of 18. 2 t/ha is comparable to those of intensively managed crops such as Eucalyptus nitens and rubber. Several sample trees had stained heartwood and soft pulpy cores and further studies are recommended.